Taiwan's Triangle: US, China, and Geopolitical Chessboard - Ahmad Khan, Samim; Rasool Mir, Musssaib (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores how the interactions between China, the USA, and their allies shape Taiwan's politics, as both nations contest each other's narratives, denying Taiwan an independent agency. It aims to expand our understanding of Taiwan's role in the escalating conflict between China and the USA, shedding light on deeper issues in the Asia-Pacific Region due to mismanaged relations. The paper argues that the U.S. and China prioritize power politics and national interests over moral considerations, influencing their international behavior and dominance over Taiwan. Taiwan is seen as a global hotspot, analyzed for its geopolitical, geo-strategic, and geo-economic impact on the Asia-Pacific Region. The historical context of Taiwan's formation is briefly explored, setting the stage for dissecting the triangular relationship. The third section summarizes the highs and lows of the U.S., China, and Taiwan relationship, emphasizing Taiwan's role in the power struggle. The paper concludes with suggestions for the research community and leaders to promote peace and discourage aggressive behaviour. Throughout, terms like Taiwan, ROC, China, and PRC are used interchangeably.